PELATIHAN DAN PENDAMPINGAN PENGELOLAAN KEUANGAN USAHA TOKO KELONTONG DI KAMPUNG KUPRIK KABUPATEN MERAUKE - Dina Fitri Septarini; Fenty Yoseph Manuhutu (Musamus University, 2019)
Training and Assessment of Business Financial Management of Grocery Stores In Kuprik Merauke. Grocery stores are one of the types of MSMEs that are mostly in the community and potentially bring profits quickly. Most grocery store owners have not understood the importance of financial management for business development and have never compiled financial statements, so they do not know exactly how much profit or loss they experience. Training on financial management of the grocery store business aims to provide knowledge on how to manage finances well and prepare the right financial reports so that store income can increase and business people can further develop their business. The methodology used in financial management training and assistance activities is lectures, case studies, discussions, and mentoring. The results of the implementation of the activity showed that financial reports were very much needed in the grocery store business in Kuprik Village. The curiosity of the owner of a grocery store in the village of Kuprik to understand and be able to compile financial statements that are very high right, but its implementation is still low because the nature of the business owned is only a side business. Keywords: financial management, grocery stores, MSMEs